Immobilization and property of penicillin G acylase on amino functionalized magnetic Ni0.3Mg0.4Zn0.3Fe2O4 nanoparticles prepared via the rapid combustion process - Ma, Mingyi; Chen, Xiu; Yue, Yao; Wang, Jie; He, Dawei; Liu, Ruijiang (Frontiers in Bioengineering and Biotechnology, 2023)
Magnetic Ni0.3Mg0.4Zn0.3Fe2O4 nanoparticles were successfully prepared by a rapid-combustion method and the nanoparticles were calcined at 400 °C for 2h. The average particle diameter of the nanoparticles was about 21.7 nm, and the saturation magnetization was around 29.2 emu/g. This material was employed as a carrier to immobilize penicillin G acylase (PGA). The surface of the nanoparticles was modified with sodium silicate hydrate, and the PGA was covalently bound to the carrier particles through the cross-linking of glutaraldehyde. The results emerged that the activity of the immobilized PGA reached a maximum of 7121.00 U/g. The optimum pH of the free PGA and the immobilized PGA was 8, and the optimal temperature of the immobilized PGA was 45 °C which is higher than the free PGA. The immobilized PGA exhibited higher stability against changes in pH and temperature. In addition, the Michaelis–Menten constant (Km) values of the free PGA and immobilized PGA were 0.00387 mol/L and 0.0101 mol/L, while the corresponding maximum rate (Vmax) values were 0.387 μmol/min and 0.129 μmol/min. Moreover, the immobilized PGA revealed excellent cycling performance.